Energy, exergy, exergoeconomic and enviroeconomic (4-E) assessment of solar water heater with/without phase change material for building and other applications: a comprehensive review - Imtiaz, Ali Laghari; Reji Kumar, Rajamony; Pandey, A. K.; Mahendran, Samykano; Chopra, Kapil; Abusorrah, Abdullah M.; Sharma, Kamal; Tyagi, V. V. (Elsevier, 2021)
Solar water heating is the most common method of using solar energy because of its technical viability and economic attractiveness. However, intermittent nature of solar energy and lack of energy storage limits use of Solar Water Heaters (SWHs). Phase change materials (PCMs) utilize the heat energy from the solar energy effectively. Integrating PCMs to SWHs overcome the limitation of limited use in the day time only and make it more efficient and user friendly. The main objective of this review paper is to review a broad variety of work on the energy, exergy, exergoeconomic and enviroeconomic (4E) approach of with and without PCMs integrated SHWs for building and other applications in recent years and to address the technical challenges associated with SWH systems. This review paper discusses the recent advances, practical techniques, appropriate specifications of solar water heating systems with and without phase change materials based on 4E (energy, exergy, exergoeconomic and enviroeconomic) analytical approach. It has been observed that solar water heater combined with PCMs are more efficient in terms of energy and exergy efficiency and energy payback period.